Three transporters, including the novel Gai1 permease, drive amino acid uptake in Histoplasma yeasts - Stephanie C. Ray; Qian Shen; Chad A. Rappleye (Virulence)
The dimorphic fungus Histoplasma capsulatum, which almost exclusively resides within host phagocytic cells during infection, must meet its nutritional needs by scavenging molecules from the phagosome environment. The requirement for gluconeogenesis, but not fatty acid catabolism, for intracellular growth, implicates amino acids as a likely intracellular nutrient source. Consequently, we investigated Histoplasma growth on amino acids. Growth assays demonstrated that Histoplasma yeasts readily utilize most amino acids as nitrogen sources but only efficiently catabolize glutamine, glutamate, aspartate, proline, isoleucine, and alanine as carbon sources. An amino acid permease-based conserved domain search identified 28 putative amino acid transporters within the Histoplasma genome. We characterized the substrate specificities of the major Histoplasma amino acid transporters using a Saccharomyces cerevisiae heterologous expression system and found that H. capsulatum Dip5, Gap3, and a newly described permease, Gai1, comprise most of Histoplasma’s amino acid import capacity. Histoplasma yeasts deficient in these three transporters are impaired for growth on free amino acids but proliferate within macrophages and remain fully virulent during infection of mice, indicating that free amino acids are not the principal nutrient source within the phagosome to support Histoplasma proliferation during infection.